Marine Engineering Innovation for Environmental Compliance: An Integrated Environmental Engineering Framework for Indonesian Domestic Vessel Operations - Susi Herawati; Marihot Simanjuntak; Larsen Barasa; Natanael Suranta; Marudut Bernadtua Simanjuntak (International Journal of Marine Engineering Innovation and Research, 2026)
Marine engineering is undergoing a fundamental redefinition — from a discipline optimized primarily for propulsive performance and fuel economy to one in which environmental engineering is integral to every shipboard system domain. This study develops an Integrated Environmental Engineering Framework (IEEF) for Indonesian domestic vessel operations, synthesizing marine engineering innovation literature across propulsion, thermal management, exhaust treatment, waste management, and hull systems into a structured, evidence-based environmental technology portfolio. A mixed-methods methodology was employed, combining quantitative Environmental Engineering Audit Protocol (EEAP) assessment of 72 Indonesian domestic vessels across 10 MARPOL-relevant engineering domains with AHP-TOPSIS multi-criteria technology assessment involving 24 domain experts. The audit reveals critical compliance gaps in CII monitoring systems (36%), waste heat recovery installation (10%), and eco-compliant antifouling coatings (35%), alongside high-severity deficits in NOₓ treatment (42%), sewage treatment (44%), and ballast water management (50%). AHP-TOPSIS ranking identifies waste heat recovery and CII digital monitoring as equal top-priority investments (composite score 0.83), followed by nano-hybrid antifouling (0.79), Annex IV sewage treatment (0.77), SCR/EGR NOₓ reduction (0.72), and LNG dual-fuel conversion (0.68). The IEEF organizes these priorities within a three-horizon implementation roadmap — Horizon 1 (2025–2027) deploying proven compliance technologies, Horizon 2 (2027–2032) advancing NOₓ reduction and hybrid system integration, and Horizon 3 (2032–2050) transitioning toward hydrogen, ammonia, fuel cell propulsion, and on-board carbon capture — providing a structured engineering trajectory aligned with IMO 2050 net-zero ambition.